IMPROVEMENT OF STUDENTS’ KNOWLEDGE AND READINESS AFTER A SHORT COURSE PILOT OF IPE IN GERIATRIC CARE - Setiawan, Ide Pustaka; Mawardi, Fitriana; Riskiyana, Rilani; Arjuna, Tony; Samekto, Perdana; Madyaningrum, Ema; Anggraeni, Vita Yanti; Ariwibowo, Eko (Universitas Gadjah Mada, 2023)
Background: A five-day interprofessional education (IPE) pilot program in geriatric care was introduced to advanced students in clinical rotation. The program focused on providing students with interprofessional experience in managing elderly care. This study aimed to understand the knowledge, readiness, and perception of students from three different professional programs (medical, nursing, and health nutrition students regarding this pilot program Methods: A descriptive quantitative research with open-ended questions was conducted. Wilcoxon analysis was performed to find the difference in students' knowledge and readiness regarding interprofessional collaboration practice before and after the pilot program. Open-ended questions were distributed online to evaluate students' reflections upon participating in the program. Results: There were 27 participants consisting of 8 medical students, 10 nursing students, and 9 health nutrition students involved in this study. The quantitative study found an increase in interprofessional knowledge and readiness (p<0.001). There were also improvements in intra-professional knowledge of the medical, nursing, and dietetics students with p<0.001 in each profession. A descriptive analysis of open-ended questions revealed that teacher competence and good program coordination were regarded as important for the program's success. Students reported that they had a better understanding of the role of other professions in managing patients’ problems. Interprofessional communication was regarded as important to ensure patient safety. Students also learned that interprofessional collaboration in elderly care is important to improve the patient’s quality of life. Conclusion: The pilot IPE program improved both interprofessional and intra-professional knowledge and readiness of the students in geriatric clinical rotation. Moreover, students felt this activity had a positive impact on their understanding of interprofessional collaboration and patient health outcomes.